Complete genome sequence of the broad-host-range Paenibacillus larvae phage phiIBB_Pl23 - Oliveira, Ana (2013)
Paenibacillus larvae is a Gram-positive bacterium that causes American foulbrood, an important disease in apiculture. We report the first complete genome sequence of a P. larvae phage, phiIBB_Pl23, isolated from a hive in northern Portugal. This phage belongs to the family Siphoviridae.